Adoption of digital payment methods in India. (11th April 2019) - Tiwari, Tanu; Srivastava, Alpana; Kumar, Surendra
India is home to 17.5% of the world's population and nearly 76% of its adult population does not understand even the basic financial concepts. Post-independence, Government of India has put continued effort to include more and more people and entities under the sphere of banking and financial services. Indian banking history has witnessed reforms, liberalisation and privatisation. Over the time innovation in digital technologies has led to adoption of digital payments to boost slow penetration of financial inclusion (FI). In this study, it has been tried to find the current state of digital financial inclusion (DFI) and reasons for its poor performance and challenges. This study can help in removing lacunas in the program and help in better implementation of DFI and there by achieving the goal of FI at broader level. Results suggest that education, awareness and internet accessing devices are three major reasons behind lower penetration of digital payments in India.